صناعة الكارثة في الأدب العربي بين الأمس واليوم: دراسة إنشائية اجتماعية - عبيد، حمدي خليفة (جامعة الأميرة نورة بنت عبد الرحمن, 2022)
رغم تعدد الكوارث والجوائح والمصائب في تاريخنا العربي والمعاصر، فإننا نكاد لا نظفر بكتانة نقدية ترسم بداية الطريق إلى هذه الخانة الأجناسية التي ما تزال فارغة، وتغطي عليها التصورات التصنيفية العربية الموسومة بالثبات. لهذا الاعتبار وتحت وقع ما نعيشه اليوم من أصداء جائحة الكورونا وما بتنا نتعايش معه من إكراهات، اخترنا دراسة علاقة الأدب قديما وحديثا، إنشاء ونقدا بالكارثة، وجعلنا من دراسة مصطلح الكارثة وما يعلق به من متصورات مفهومية منطلقا لنا، طالما أن المصطلح من حيث هو مواضعة ثانية داخل اللغة يحتفظ بذاكرة خاصة، من شأنها أن تنير لنا سبل الدراسة. ولقد استرفدنا هذه المتصورات في تعرف المكونات الإنشائية المساهمة في صناعة الكارثة. ومتى توضحت لنا ملامحها صرفنا اهتمامنا إلى تسليط الضوء على بعض الأجناس الأدبية المتوافرة على مقومات الصناعة الأدبية للكارثة. أما مقاربتنا فكانت مقاربة إنشائية اجتماعية. وذلك لما في الكارثة ذاتها من تشعب يقتضي الفهم لا التفسير الأحادي. Despite the multiplicity of disasters, and catastrophes, in our Arab history, we do not find critical writing related to disaster literature. That’s why our research is concerned with identifying the semantic and conceptual term related to "catastrophe or disaster". Especially, since both the expression and the term retain a special semantic memory that helps us to monitor the structural components that contribute to the disaster in literature. when the features of these components became clear to us, we moved on to identify some of the ancient and modern literary genres available on the components of the literary genre of catastrophe. As for the approach used in the study, it was a structural and social approach, due to the complexity of the catastrophe itself that requires comprehensive understanding rather than a singular interpretation. Among the most important recommendations of our research are: Researching the writings of collective pain by focusing on the literary genres that are available on what we have termed the catastrophic perspective.
Keywords: الأدب العربي -- الأدب العربي -- فيروس كورونا (كوفيد-19)